Implementation of Basic Continuity and Recovery Plan, Teacher Engagement, and Parental Involvement in Public Secondary School: A Basis for School-Home Framework - Mary Jane Corpuz (Research Synergy Foundation, 2024)
As the face-to-face classes progress schools reopen their ground for the school year 2022-2023. Although expected, it is discovered that many learners do not meet the expected outcomes in mastery of basic numeracy and literacy skills and competencies. The Department of Education instantly developed a recovery learning plan framework to guide schools in addressing learning gaps. The main thrust of this paper was to determine the level of implementation of the Basic Continuity and Recovery Plan, Teacher Engagement, and Parental Involvement in public schools. The findings of the study revealed that the implementation level of basic continuity and recovery plan as assessed by the school head in terms of the development and implementation of long-term and catch-up plans to accelerate learning and reintegration of learners’ safe return to the school system was implemented. in terms of establishment of teachers' and learners' support systems through community and stakeholders' collaboration, literacy and numeracy assessment levels and learners' overall situation, especially the marginalized and modification learning package focused on fundamental skills towards resiliency were fully implemented. The level of teacher engagement in terms of vigor, dedication, and absorption were very often. The level of parental involvement was highly involved. There was no significant difference amongst respondents’ assessment on Implementation of Basic Continuity and Recovery Plan, Teacher Engagement, and Parental Involvement. There was a significant relationship between basic continuity and recovery Plan, teacher engagement and parental involvement. A localized School-Home Framework that focused on the four pillars of school-home partnership and connection was proposed.